2020
DOI: 10.1186/s13073-020-00735-4
|View full text |Cite
|
Sign up to set email alerts
|

Shallow whole-genome sequencing of plasma cell-free DNA accurately differentiates small from non-small cell lung carcinoma

Abstract: Background: Accurate lung cancer classification is crucial to guide therapeutic decisions. However, histological subtyping by pathologists requires tumor tissue-a necessity that is often intrinsically associated with procedural difficulties. The analysis of circulating tumor DNA present in minimal-invasive blood samples, referred to as liquid biopsies, could therefore emerge as an attractive alternative. Methods: Concerning adenocarcinoma, squamous cell carcinoma, and small cell carcinoma, our proof of concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…At the biologic level, the potential utility of copy number profiling and the t-MAD score for monitoring NSCLC and other tumour entities [ 23 , 38 , [44] , [45] , [46] ] is based on their correlation with the fraction of ctDNA among cfDNA, which makes them a surrogate of tumour burden irrespective of the specific mutations present. In addition, copy number profiling of cfDNA has been used for histological classification of lung tumours [47] and as an early indicator of immunotherapy response [48] . More recently, longitudinal monitoring of genomic copy number from cfDNA in patients with small-cell lung cancer [49] , squamous lung cancer [50] and metastatic castration resistant prostate cancer [51] revealed the utility of this approach for early detection of disease progression and identification of genomic events associated with therapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…At the biologic level, the potential utility of copy number profiling and the t-MAD score for monitoring NSCLC and other tumour entities [ 23 , 38 , [44] , [45] , [46] ] is based on their correlation with the fraction of ctDNA among cfDNA, which makes them a surrogate of tumour burden irrespective of the specific mutations present. In addition, copy number profiling of cfDNA has been used for histological classification of lung tumours [47] and as an early indicator of immunotherapy response [48] . More recently, longitudinal monitoring of genomic copy number from cfDNA in patients with small-cell lung cancer [49] , squamous lung cancer [50] and metastatic castration resistant prostate cancer [51] revealed the utility of this approach for early detection of disease progression and identification of genomic events associated with therapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Raman et al (2020) suggests shallow whole genome sequencing for tumour subtyping of advanced lung cancer as an alternative to eliminate invasive tumour histology subtyping. In this study, 86.3% of CNV were detected using NGS and successfully detected the different subtypes to initiate treatment strategies [36] .…”
Section: Artificial Intelligence and Precision Oncology In Healthcarementioning
confidence: 85%
“…This approach reduces cost of sequencing without compromising the biological data obtained for obtaining accurate clinical insights [34] . Furthermore, shallow sequencing has also been applied to the whole genome for diagnostics in breast cancer [35] , lung cancer [36] and neuroblastoma [37] . For detection of copy number variations (CNV) in breast cancer, the authors implemented shallow whole genome sequencing using FFPE samples.…”
Section: Artificial Intelligence and Precision Oncology In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that shallow whole genome sequencing (sWGS) with low coverage (~ 0.5 X) can be used to pro le cfDNA and ctDNA. Several studies of various cancers [3][4][5][6][7] demonstrated the feasibility of sWGS to identify biomarkers. Based on these studies, we hypothesized that whole exome sequencing (WES) of blood from cancer patients could reveal overall survival prognosis.…”
Section: Introductionmentioning
confidence: 99%